EFEKTIFITAS PENGELOLAAN PAJAK HIBURAN PADA DINAS PENDAPATAN DAERAH KOTA MANADO - Gaol, Ropintauli Lumban; POSUMAH, JOHNNY HANNY; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2016)
in the management of the entertainment tax in the Department of Revenue of Manado is the level of awarenessof taxpayers who pay taxes are still low in entertainment, still less employees in dealing with the entertainmenttax and lack of socialization to the taxpayer itselfThis study uses descriptive qualitative approach through in-depth interviews to 9 informants, observation andsearch for additional documents in the form of a list of guidelines for the interview, a tape recorder andstationery.The results showed that the effectiveness of Management of Entertainment Tax On Revenue Office of ManadoCity has not been effective.Keywords: Effectiveness of Management of Entertainment Tax